KARAKTERISTIK GEOMORFOLOGI KAITANNYA DALAM PENENTUAN LOKASI RAWAN BENCANA LONGSOR DI CIKARANG DAN SEKITARNYA, KECAMATAN CISEWU, KABUPATEN GARUT, PROVINSI JAWA BARAT - Sri Wahyuni; Emi Sukiyah (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2023)
The potential for landslide in Cisewu area is included in the medium-high landslide potential zone. Cisewu area has a hilly landscape composed of Quaternary volcanic material. The existence of geological structures such as joint and faults increases the risk of landslides, especially during the rainy season. This research aims to identify and analyze geomorphological characteristics and their relation in determining the location of landslide prone disasters. Research activities were conducted through a studio analysis using remote sensing methods with satellite imagery. The geomorphological aspects studied consist of slopes, drainage patterns, lithology and land use. Based on the results of interpretation, it is known that the research area has morphological characteristics of gentle to steep hills and drainage patterns influenced by geological structures. The research area is composed of volcanic products with a predominance of land use such as forests, plantations and fields, shrubs, rice fields and residential. Based on field observations, it is known that the research area has the potential for rockfall and translational landslide. Therefore, it is necessary to have good regional planning to minimize the impact of landslides in the future.